Incidencia de la Neoplasia Intraepitelial Prostática en hombres de 40 a 80 años que acuden a consulta externa en SOLCA de Machala de abril a septiembre de 2006 - Atiencia Armijos, Priscilla A. (2007)
Most of the cases of prostate cancer are caused by the variety denominated adenocarcinoma (cancer that arises starting from the cells that constitute the glandular part of the prostate). A value of PSA up 4 nanogramos for milliliters (ng/ml) it is considered normal for a man average.